2010
DOI: 10.1007/s11695-010-0269-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hyperhomocysteinemia After Gastric Bypass Surgery in Obese Subjects

Abstract: The main determinants of homocysteine concentration identified in this study are folate and serum creatinine. Multivitamin supplementation with a high dose of folate prevents hyperhomocysteinemia after GBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…However, no difference in the serum homocysteine concentrations between obese and nonobese subjects has also been reported [7,8]. Gomez-Ambrosi et al [9], Ledoux et al [10], and our group [6] did not observe significant changes in serum homocysteine concentrations after bariatric surgery, while other studies showed decrease [11,12] or increase [13][14][15][16][17] in serum homocysteine concentrations after bariatric surgery. Such variation in serum homocysteine concentration after bariatric surgery suggests that serum homocysteine concentrations are affected by factors such as different compositions and amounts of food intake.…”
Section: Introductioncontrasting
confidence: 39%
“…However, no difference in the serum homocysteine concentrations between obese and nonobese subjects has also been reported [7,8]. Gomez-Ambrosi et al [9], Ledoux et al [10], and our group [6] did not observe significant changes in serum homocysteine concentrations after bariatric surgery, while other studies showed decrease [11,12] or increase [13][14][15][16][17] in serum homocysteine concentrations after bariatric surgery. Such variation in serum homocysteine concentration after bariatric surgery suggests that serum homocysteine concentrations are affected by factors such as different compositions and amounts of food intake.…”
Section: Introductioncontrasting
confidence: 39%
“…These data collectively suggest that elevated plasma Hcy levels may be associated with increased adiposity in this animal model. In fact, the association between HHcy and obesity has been reported, although conflicting results exist (6,19,21,32). Long-term time course studies are required to establish a potential causal connection between increased Hcy and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our in vivo observations may not extend to other experimental models. This heterogeneity may also account for controversial reports on the association between HHcy and obesity (6,19,21,32).…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for treating iron deficiency in bariatric surgery patients are reviewed by Munoz et al (278 [EL 4, review]). Guidelines for folic acid and B 12 are based on maintenance of biochemical and functional markers (e.g., homocysteine, RBC folate, and methylmalonic acid) within target ranges (279 [EL 2, PCS]; 280 [EL 3, SCR]). Calcium intake primarily in the form of food is advocated in LAGB given recent reports linking calcium supplementation with increased incidence of MI risk in postoperative women (281 [EL 2, PCS])).…”
Section: Evidence Basementioning
confidence: 99%